2009
DOI: 10.1111/j.1423-0410.2009.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking blood products in blood centres using radio frequency identification: a comprehensive assessment

Abstract: Radio frequency identification application has significant process-orientated and technological implications. It is feasible and economically justifiable to incorporate RFID into blood centre processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 15 publications
0
61
0
10
Order By: Relevance
“…After redesign of the blood transfusion chain, the RFID system and methods presented in this study will then allow follow-up assessments of the effects of these efforts on the quality of the blood transfusion chain in the AMC. Other studies have successfully implemented RFID technology in blood transfusion medicine [10,12,16,[27][28][29][30], but did not focus on revealing the merits of RFID in assessment of the compliancy to blood chain quality guidelines, including those prescribing logistic and temperature constraints. Sandler showed that RF microchips can collect key data concerning for example the donor, the manufacturing, laboratory test results and expiration data during blood collections, can facilitate information transfer between blood centres and hospitals and confirm recipient blood unit match at the bed side [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After redesign of the blood transfusion chain, the RFID system and methods presented in this study will then allow follow-up assessments of the effects of these efforts on the quality of the blood transfusion chain in the AMC. Other studies have successfully implemented RFID technology in blood transfusion medicine [10,12,16,[27][28][29][30], but did not focus on revealing the merits of RFID in assessment of the compliancy to blood chain quality guidelines, including those prescribing logistic and temperature constraints. Sandler showed that RF microchips can collect key data concerning for example the donor, the manufacturing, laboratory test results and expiration data during blood collections, can facilitate information transfer between blood centres and hospitals and confirm recipient blood unit match at the bed side [10].…”
Section: Discussionmentioning
confidence: 99%
“…Also, information about objects tagged with for example RFID can be transmitted for multiple objects simultaneously, through physical barriers and from a distance, something which is impossible to realize with barcodes [22]. RFID further enables automated monitoring of the location and storage temperature of blood products within the distribution chain of a facility or during transportation [12,22]. Finally, the implementation of RFID in the blood transfusion chain could, for instance reduce the number of incorrect blood components transfused (IBCT) by using smart pumps that read RFID-coded data placed on blood bags and a patient's wristband [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations